Analysis of the qualitative characteristics of the waters of the Tanjiro River and their impact on different uses - AlIbrahimi, Suhaila; Nagy, Zahraa (Al-Adab Journal, 2023)
Knowing the qualitative characteristics of water is of great importance because the physical and chemical characteristics determine the quality of water and the field that can benefit from this water. Water quality depends on several interrelated and interrelated factors, which include the climate, the geological situation in the region, the topographical and hydrological situation of the basin area, the content of negative and positive ions and other elements, which determine the dominance of certain processes in the water and their relative importance varies significantly due to the difference in use within the drainage basin and that These elements do not only determine the use of water, but also determine the area in which it represents the most benefit from water.